2007
DOI: 10.1039/b700631d
|View full text |Cite
|
Sign up to set email alerts
|

Quantum chemistry-based NMR spin Hamiltonian parameters of GABA for quantitation in magnetic resonance spectroscopy

Abstract: Chemical shifts delta and spin-spin coupling constants J have been calculated using quantum chemistry approaches for the gamma-amino butyric acid GABA which is a brain metabolite. Two theoretical methods HF and DFT/B3LYP, two basis sets 6-31G* and 6-311+G(2d,p) and two gauge-invariant methods CSGT and GIAO have been used. From delta and J values, NMR spectra have been obtained from the strongly coupled spin system Hamiltonian using the NMR-SCOPE package. Solvent effects have been considered within the polarisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…and are given in Table . These values were estimated from high‐resolution NMR data of a GABA sample using PERCH (Kuopio, Finland) automated consistency analysis software and, in comparison with previously published chemical shifts and coupling constants , were shown to produce simulated spectra which best agreed with experimental high‐resolution GABA spectra recorded at high magnetic field strength.…”
Section: Methodsmentioning
confidence: 99%
“…and are given in Table . These values were estimated from high‐resolution NMR data of a GABA sample using PERCH (Kuopio, Finland) automated consistency analysis software and, in comparison with previously published chemical shifts and coupling constants , were shown to produce simulated spectra which best agreed with experimental high‐resolution GABA spectra recorded at high magnetic field strength.…”
Section: Methodsmentioning
confidence: 99%
“…1 H and 13 C NMR spectroscopy in DMSO-d6 solution of muscimol was selected as source of experimental information of muscimol molecular structure in solution. The current approach is partly similar to recent theoretical and experimental 1 H NMR studies on GABA 51 , as well as cytosine and 1-methylcytosine in solution 54 . However, in our study the analysis of the observed NMR data was supported by high-level DFT calculations combined with fairly complete basis sets and using both equilibrium and rovibrationally averaged geometry [59][60][61][62] .…”
mentioning
confidence: 62%
“…From these studies emerges that in the presence of water GABA could exist as zwitterion [51][52][53] . However, this form is only slightly more stable than the neutral form and the results are strongly method and basis set dependent.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Being currently involved in calculations of NMR spin Hamiltonian parameters for metabolites [3][4][5], in order to produce reliable values of these parameters from which NMR spectra could be simulated and used further in quantitation procedures, we investigated sarcosine in the present study.…”
Section: Introductionmentioning
confidence: 99%